From grassroots to international markets: a qualitative study of marginalized entrepreneurs in India - Saiyed Abrar Ali; Wierenga Marleen; Fernhaber Stephanie A.; Nummela Niina (Elsevier (Commercial Publisher), 2025)
Much of the growing literature on international entrepreneurship focuses on how positive circumstances, such as having prior international experience, business networks, or formal institutions lead to international entrepreneurial action and overlooks the role more challenging circumstances might play. In this study, we extend and refine challenge-based entrepreneurship theory to explore what influences international entrepreneurial action undertaken by marginalized entrepreneurs in an emerging economy. Despite widening economic and social disparities in emerging economies, little is known about entrepreneurs who have traditionally been “left behind.” Our findings suggest that these marginalized entrepreneurs have not only a set of liabilities but also advantages, including creative problem solving and perseverance, as well as local knowledge and networks. To spur the first-person international opportunity belief associated with international entrepreneurial action, an intermediary with resources and networks is needed to offset the liabilities. These intermediaries act as gatekeepers, helping some marginalized entrepreneurs but holding back others.